TEACHING RECEPTIVE AND PRODUCTIVE SKILLS FOR NON-LINGUISTIC LEARNERS - Murotova, Gulnoz (Журнал иностранных языков и лингвистики, 2023)
This research paper reveals the issues of training students of non-linguistic universities in the discipline “Foreign language”. Poor results in foreign language are mediated by two main factors: insufficient time for practical work by the lack of language environment and low motivation to study the subject, as well as an imbalance between independent and classroom work. The aim of the study is to develop a methodology that takes into account the specifics of technical university and aimed at combining independent and practical work.